2015
DOI: 10.1021/acs.chemmater.5b02335
|View full text |Cite
|
Sign up to set email alerts
|

Features of KF and NaF Postdeposition Treatments of Cu(In,Ga)Se2 Absorbers for High Efficiency Thin Film Solar Cells

Abstract: The introduction of a KF post-deposition treatment (KF PDT) of Cu(In,Ga)Se 2 (CIGS) thin films has led to the achievement of several consecutive new world record efficiencies up to 21.7% for the CIGS solar cell technology. The beneficial effect of the KF PDT on the photovoltaic parameters was observed by several groups in spite of differing growth methods of the CIGS layer. For CIGS evaporated at lower temperature on alkali-free, flexible plastic substrates, a postdeposition treatment to add Na was already suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
200
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 180 publications
(221 citation statements)
references
References 43 publications
19
200
2
Order By: Relevance
“…For the NaF/KF-PDT CIGSe samples, we detect no Na signal, which may be due to the suggested "ion-exchange mechanism" explaining that K replaces Na in the CIGSe during the PDT. [7], [18] Comparing the two NaF/KF-PDT CIGSe absorbers, it is apparent that for the alkali-poor NaF/KF-PDT CIGSe the intensity of the K-related photoemission signals (K 2s and K 2p) is significantly lower than the respective peak intensities for the alkali-rich NaF/KF-PDT CIGSe (see also Fig. 3c2)).…”
Section: Methodsmentioning
confidence: 94%
“…For the NaF/KF-PDT CIGSe samples, we detect no Na signal, which may be due to the suggested "ion-exchange mechanism" explaining that K replaces Na in the CIGSe during the PDT. [7], [18] Comparing the two NaF/KF-PDT CIGSe absorbers, it is apparent that for the alkali-poor NaF/KF-PDT CIGSe the intensity of the K-related photoemission signals (K 2s and K 2p) is significantly lower than the respective peak intensities for the alkali-rich NaF/KF-PDT CIGSe (see also Fig. 3c2)).…”
Section: Methodsmentioning
confidence: 94%
“…Semiconductor surfaces, especially semiconductor-metal interfaces, can host several interface defects, leading to high surface recombination velocities, which in turn lower the electrical performance of solar cells. [36,37] These findings have motivated device simulations that have predicted gains up to 3% (in absolute power conversion efficiency) in fully passivated solar cells. The field effect passivation occurs by the presence of a built-in electric field that arises from the high density of fixed charge from the commonly used dielectric materials of the passivation layer.…”
Section: Introductionmentioning
confidence: 91%
“…Werner et al investigated a large set of samples with various PDTs and showed that the main capacitance step has the same origin independent of the alkaline PDT and is consistent with the capacitance step labeled "N1." [27] To extract the drop in capacitance and the activation energy of the capacitance step, the fitting method proposed by Weiss et al is applied to the capacitance spectra. [28] The activation energies of the main capacitance step show a good correlation to the incorporated Rb amount as depicted in Figure 7a.…”
Section: Injection Barrier Formationmentioning
confidence: 99%